Мадей песятайлэн выжыкылъесыз: сценариийес, пьесаос / Р. П. Николаева - Николаева Римма Павловна (Удмуртия, 2018)
Экземпляры: ф.1 (2018) / Инвентарный номер: 54882 / Цена: / Сис.шифр: К84(2Рос=Удм)-6 / Авт.знак: Н 63 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Удм)-6